An examination of the role of spatial ability in the process of problem solving in chemical engineering. Issue 1 (2nd January 2020) - Sorby, Sheryl A.; Duffy, Gavin; Loney, Norman
ABSTRACT: Engineers often communicate with one another through drawings or sketches and understanding technical information through graphical representations is a skill necessary for engineering practice. Well-developed spatial skills are known to be important to understanding technical drawings and are therefore, important to success in engineering. Unfortunately, of all cognitive processes, spatial skills show robust gender differences, favouring males, which could contribute to the underrepresentation of women in engineering. In this research, we administered a test of spatial cognition to students enrolled in a common 3rd year course in chemical engineering . In a second session, students were given a set of 12 textbook problems from a prerequisite course to solve, to determine if there was a link between scores on a spatial instrument and the number and type of problems solved correctly. Both instruments were scored and statistical analyses were performed. A strong positive correlation (r = 0.59, p < 0.00001) between spatial skills test scores and the number of problems successfully solved by the students was found, confirming the link between spatial skills and engineering problem-solving. This paper describes the findings from this research, including identification of the type of problems where spatial skills appear to play a role.